Regulatory and Policy Analysis of Production, Development and Use of Sustainable Aviation Fuels in the United States - Korkut, Ekrem; Fowler, Lara B. (Frontiers in Energy Research, 2021)
The United States, spurred in part by international developments, is expanding its law and policy to incentivize the use of sustainable aviation fuels. While the U.S. has agreed to participate in the International Civil Aviation Organization’s (ICAO’s) Carbon Offsetting and Reduction Scheme for International Aviation (CORSIA), it has only recently adopted federal rules that define greenhouse gas emission reduction standards for certain classes of airplanes (effective January 2021). However, such standards focus on engine efficiency rather than the fuel burned. For sustainable aviation fuels, the U.S. continues to rely on voluntary programs at a federal, state, and regional level. The federal Renewable Fuel Standard program allows producers to opt in. In addition, states have started to allow sustainable aviation fuel producers to “opt in” to their programs; this includes California’s Low Carbon Fuel Standard, Oregon’s Clean Fuels Program, and Washington’s newly adopted Clean Fuels Program. Other states are also starting to consider such programs. Elsewhere, states like Hawaii are starting to support SAF production in other ways, including through tax mechanisms. In addition, regional and private efforts to adopt and/or promote sustainable aviation fuels are underway. This piecemeal approach—due in part to the lack of cohesive U.S. federal policy—stands in contrast to the European Union’s Renewable Energy Directive and Emissions Trading System, and adoption of policies by European countries. Because of aviation’s international nature, tracking what is happening in Europe matters greatly for U.S. carriers. As the U.S. works to meet its international obligations through CORSIA, finding a way forward with sustainable aviation fuel in the United States may depend on a more defined federal policy. Actions taken by both the EU and European countries offers some guidance for actions that could be taken by the U.S. Even in the absence of more defined measures, better tracking of voluntary measures is a critical step.